Dilema Kepemilikan Sertipikat Ganda: Kasus Kontroversial Obyek Tanah - Rusman Rusman; Aksah Kasim; Andi Heridah; Johamran Pransisto (Jurnal Litigasi Amsir, 2024)
This study aimed to identify the causes of dual land certificate ownership and explore solutions to this issue, utilizing a normative-empirical research approach. The findings indicate that dual certificates often result from landowners' negligence in managing their property, leading to unauthorized takeover by others. Additionally, flaws in the National Land Agency's system, lack of a comprehensive land database, and inaccurate or missing local government records contribute to the problem. Solutions include direct negotiation or mediation between parties, with the option of legal action through the State Administrative Court if unresolved.